(untitled) (American Journal of Islam and Society, 2002)
Today, politicians and political activists of every stripe recognize the power of the international media. From the most gilded generalissimo to the grulr biest guerrilla, there are few who would pass up a chance to plead their case on the world stage. This has given foreign correspondents, particularly those from first world countries like the United States, easy access to movers and shakers across the globe. Unfortunately, understanding does not always come with access. Nowhere has this lack of understanding been more pervasive- or more pernicious - than among those reporters covering the Islamic world. Joyce M. Davis, deputy foreign editor for Knight Ridder newspapers and former deputy senior editor at National Public Radio, sets out to remedy this prolr lem in her book, Between Jihad and Salaam: Profiles in Islam. Through interviews with 17 "Islamic leaders," Davis endeavors "to help us understand the intellectual vitality that is now igniting the Muslim world." However, like too many of her colleagues, the author quickly becomes lost in the surface realities of that world. In the end, her book does little to challenge the stereotypes and misconceptions she promises to shatter. Davis begins the book with an introduction that outlines her mission while revealing the limits of her own understanding. While she deftly dispels some of the more blatant misunderstandings about Islam, she also throws around technical terms like "lslamists" and "scholars" without ...